Feasibility Study: Potentcy of Service Development at Taman Husada Public Hospital, Bontang City- East Kalimantan - Paramita, Tri Ratna; Adrianto, Ratno; Ramdan , Iwan M. (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Health as a basic human right is an important thing in life. Legally, the government is responsible for ensuring that the health of citizens is fulfilled. The right of citizens to obtain health services can be seen from the provision of health facilities. Based on regulations, as a health service facility, hospitals are required to provide facilities and infrastructure according to the provisions. Taman Husada Hospital as a class B referral hospital needs to adjust facilities and infrastructure according to regulations and meet the needs of the community for service development through a feasibility study. Objective : This study was conducted to obtain an overview of the potential for service development at Taman Husada Hospital so that it could provide recommendation for hospital development planning policies Research Methods/ Implementation Methods : Primary data were collected with questionnaires, analyzed descriptively quantitatively and presented through tables and narratives Results : All of respondents were not satisfied with the inpatient facilities, where 85.2% of respondents had difficulty in getting an inpatient room, and 59.3% of respondents had problems with waiting time for an inpatient room Conclusion/Lesson Learned : The condition of inpatient care and supporting facilities have not met the needs of the community at this time and all respondents provided support for the construction of new buildings and the addition of supporting facilities. It is expected that the hospital can improve inpatient services by increasing the capacity and quality of inpatient facilities, managing patient flow and adding supporting facilities